Making the match between content and foreign language: A case study on university students' opinions towards CLIL - M. Teresa Martin de Lama (Laureate Education Inc, 2015)
The present article intends to show the positive evaluation of post-graduate university students at a Spanish university after the curricular integration experience and the application of CLIL scaffolding techniques. It also aims to identify areas of methodological improvements and recommendations in the application of CLIL in the referred programme as well as in higher education contexts. The researchers used a cross-sectional study to survey the students' opinion on ICL after the integration of the syllabus of one foreign language subject and another content subject in a post-graduate degree at a private Spanish university in Madrid (Spain). The results point to a positive view of CLIL from Spanish higher education post-graduate students. The survey results also seem to show the students' confidence in CLIL for their English-led classes aids them to simultaneously increase their foreign language acquisition and their nonlinguistic contents learning. However, researchers detected certain linguistic scaffolding aspects appear to need further students' training and teachers' methodological adjustments, as they can negatively affect learners' engagement and hence, their learning outcomes. The authors note more research is needed to collect data from a wider population and increase the reliability of the results. DOI: 10.18870/hlrc.v5i1.232